2015
DOI: 10.25077/jka.v4i1.173
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Sistem Pelaksanaan Kelas Ibu Hamil di Puskesmas Malalak dan Biaro Kabupaten Agam

Abstract: AbstrakKelas ibu hamil merupakan sarana belajar bersama bagi ibu hamil agar memperoleh pengetahuan yang cukup untuk mencegah komplikasi, meningkatkan cakupan kunjungan ibu hamil dan melakukan persalinan pada tenaga kesehatan. Tujuan penelitian ini adalah untuk menganalisis sistem pelaksanaan kelas ibu hamil di Puskesmas Malalak dan Biaro Kabupaten Agam. Ini adalah suatu penelitian deskriptif kualitatif dengan melakukan wawancara terhadapa informan penelitian yang terdiri dari kepala dan kasie KIA (Kesehatan ib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…In contrast with our findings, a retrospective study involving one term of childbirth education classes to manage the risk of labor difficulty reported that the classes were significantly effective in lowering the risk of vacuum extraction, but did not have the same effect on reducing the cesarean rate.21 A study evaluating prenatal education stated 232 Putri, Mahindra, Sampurna et al Indones J Obstet Gynecol that the program could not be carried out to maximize the benefits because there would be many considerations, such as the cultural and community background of the women and the healthcare providers' method of encouraging pregnant women to join. 25 Therefore, pregnancy classes conducted according to the guidelines is aiming for the detection, prevention, and elimination of abnormalities in pregnancy, which can be complicating factors during the delivery process. The implementation of the program has its weaknesses the role of the Health Service has not been optimal in encouraging the implementation of this program, including a lack of operational support facilities and intensive facilitator training, which can be burdensome for primary healthcare (PHC) services.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with our findings, a retrospective study involving one term of childbirth education classes to manage the risk of labor difficulty reported that the classes were significantly effective in lowering the risk of vacuum extraction, but did not have the same effect on reducing the cesarean rate.21 A study evaluating prenatal education stated 232 Putri, Mahindra, Sampurna et al Indones J Obstet Gynecol that the program could not be carried out to maximize the benefits because there would be many considerations, such as the cultural and community background of the women and the healthcare providers' method of encouraging pregnant women to join. 25 Therefore, pregnancy classes conducted according to the guidelines is aiming for the detection, prevention, and elimination of abnormalities in pregnancy, which can be complicating factors during the delivery process. The implementation of the program has its weaknesses the role of the Health Service has not been optimal in encouraging the implementation of this program, including a lack of operational support facilities and intensive facilitator training, which can be burdensome for primary healthcare (PHC) services.…”
Section: Discussionmentioning
confidence: 99%
“…A Research by A Nurdiyan, YY Yulizawati, LE Bustami, D Iryani in 2014 conclude that Antenatal class is a way for pregnant women to study together to obtain proper knowledge, for preventing from complication, increasing coverage of antenatal visits, and having child delivery at the health care practitioner and also prepare women for delivery. In every visit of antenatal class Women and father fasilitate to increase their understanding about what happen during labor and delivery, so that by followong antenatal class regularly Women and family will be more prepare to do normal delivery (Nurdiyan, A et al 2014) Associated with the income, according to the NCO et al (2015) husband who works is known to also have an effect on the readiness of the birthing woman. Women with low incomes husbands would feel less need to birth preparedness plans carried out and could not be implemented due to financial constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Based on research by A Research by A Nurdiyan, YY Yulizawati, LE Bustami, D Iryani in 2014 stated that support of health service department in many health programme is important to run the programm throughly, without the support, monitoring and supervision by health service department the programme will not run properly. But they also said that the competency of Midwives to run the programme is also important because it is the responsibility of midwives to make sure that the programme is effective and efficient (A Nurdiyan, YY Yulizawati, LE Bustami, D Iryani, 2014) Health Service's support is one of the strengthening factors for a health worker, especially midwife in giving vitamin A to postpartum mother. This support can be an explanation of the time and place of vitamin A division by the Health Service or the Head of the Puskesmas, providing postpartum vitamin A capsules for the midwife, a coordination meeting to monitor the coverage of vitamin A coverage in the postpartum monthly, midwives in carrying out vitamin A delivery to postpartum and attention to the success of nutrition and health programs conducted by midwives.…”
Section: Correlation Between District Health Service's Support In Thementioning
confidence: 99%